Community turnover by composition and climatic affinity across scales in an alpine system - Smithers, Brian V.; Oldfather, Meagan F.; Koontz, Michael J.; Bishop, Jim; Bishop, Catie; Nachlinger, Jan; Sheth, Seema N. (American journal of botany, 2020)
Premise Examining community turnover across climate gradients at multiple scales is vital to understanding biogeographic response to climate change. This approach is especially important for alpine plants in which the relative roles of topographic complexity and nonclimatic or stochastic factors vary across spatial scales. Methods We examined the structure of alpine plant communities across elevation gradients in the White Mountains, California. Using community climatic niche means (CCNMs) and measures of community dissimilarity, we explored the relation between community composition and elevation gradients at three scales: the mountain range, individual peaks, and within elevation contours. Results At the mountain range scale, community turnover and CCNMs showed strongly significant relations with elevation, with an increase in the abundance of cooler and wetter‐adapted species at higher elevations. At the scale of single peaks, we found weak and inconsistent relations between CCNMs and elevation, but variation in community composition explained by elevation increased. Within the elevation contours, the range of CCNMs was weakly positively correlated with turnover in species identity, likely driven by microclimate and other site‐specific factors. Conclusions Our results suggest that there is strong environmental sorting of alpine plant communities at broad scales, but microclimatic and site‐specific, nonclimatic factors together shape community turnover at finer scales. In the context of climate change, our results imply that community–climate relations are scale‐dependent, and predictions of local alpine plant range shifts are limited by a lack of topoclimatic and habitat information.